HOXB4 Mis-Regulation Induced by Microcystin-LR and Correlated With Immune Infiltration Is Unfavorable to Colorectal Cancer Prognosis - Wang, Lingqiao; Jin, Huidong; Zeng, Yi; Tan, Yao; Wang, Jia; Fu, Wenjuan; Chen, Weiyan; Cui, Ke; Qiu, Zhiqun; Zhou, Ziyuan (Frontiers in Oncology, 2022)
Microcystin-LR (MC-LR) exists widely in polluted food and water in humid and warm areas, and facilitates the progression of colorectal cancer (CRC). However, the molecular mechanism associated with the MC-LR-induced CRC progression remains elusive. The purpose of this study is to explore the role of the hub genes associated with MC-LR-induced CRC development at the molecular, cellular and clinical levels through bioinformatics and traditional experiments. By utilizing R, we screened and investigated the differentially expressed genes (DEGs) between the MC-LR and the control groups with the GEO, in which, HOXB4 highly expressed in MC-LR-treated group was identified and further explored as a hub gene. With the aid of TCGA, GEPIA, HPA, UALCAN, Cistrome, and TIMER, the increased mRNA and protein levels of HOXB4 in CRC tissue were found to be positively associated with high tumor stage and poor prognosis, and were linked to immune infiltration, especially tumor-associated macrophages and cancer-associated fibroblasts. Cox regression analysis and nomogram prediction model indicated that high HOXB4 expression was correlated to poor survival probability. To elucidate the mechanism of high HOXB4 expression induced by MC-LR, we overlapped the genes involved in the MC-LR-mediated CRC pathways and the HOXB4-correlated transcription genes. Importantly, C-myc instead of PPARG and RUNX1 promoted the high expression of HOXB4 through experiment validation, and was identified as a key target gene. Interestingly, C-myc was up-regulated by HOXB4 and maintained cell cycle progression. In addition, MC-LR was proved to up-regulate HOXB4 expression, thus promoting proliferation and migration of Caco2 cells and driving the cell cycle progression. In conclusion, MC-LR might accelerate CRC progression. In the process, MC-LR induced C-myc augmentation elevates the high expression of HOXB4 through increasing the S phase cell proportion to enhance Caco2 cell proliferation. Therefore, HOXB4 might be considered as a potential prognostic biomarker for CRC.